2011
DOI: 10.1177/0093854811402300
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Changes in LSI-R Scores Over Time: Making the Case for Needs-Based Case Management

Abstract: The Level of Service Inventory—Revised (LSI-R) is an actuarially derived risk assessment instrument with a demonstrated reputation and record of supportive research. It has shown predictive validity on several offender populations. Although a significant literature has emerged on the validity and use of the LSI-R, no research has specifically examined change scores or the dynamics of reassessment and its importance with respect to case management. Flores, Lowenkamp, Holsinger, and Latessa and Lowenkamp and Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 28 publications
3
55
1
Order By: Relevance
“…However, few studies have examined whether risk assessment scores change over time nor whether such changes actually increase or decrease future offending (with almost no research on changes in risk assessment scores as the result of targeted intervention and subsequent reoffending). The majority of notable exceptions have examined changes in adult probationers using the Level of Service Inventory-Revised (LSI-R; Raynor, 2007;Schlager & Pacheco, 2011;Vose et al, 2009). Raynor (2007), using the LSI-R, examined changes in the composite score and subsequent official offending in a sample of 360 adult probationers.…”
Section: Risk Assessment Change Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have examined whether risk assessment scores change over time nor whether such changes actually increase or decrease future offending (with almost no research on changes in risk assessment scores as the result of targeted intervention and subsequent reoffending). The majority of notable exceptions have examined changes in adult probationers using the Level of Service Inventory-Revised (LSI-R; Raynor, 2007;Schlager & Pacheco, 2011;Vose et al, 2009). Raynor (2007), using the LSI-R, examined changes in the composite score and subsequent official offending in a sample of 360 adult probationers.…”
Section: Risk Assessment Change Scoresmentioning
confidence: 99%
“…While tying change scores to outcomes, these studies examined only the composite score leaving questions of which needs to target for the best chances of success unanswered. Schlager and Pacheco (2011) examined both total score change and domain-level score (subcomponent score) changes, again using the LSI-R, in a sample of adult male and female parolees. As they aptly noted, there remains a need to examine changes in risk assessment scores to see whether services reduce risk factors of reoffending (see also Lowenkamp & Betchel, 2007).…”
Section: Risk Assessment Change Scoresmentioning
confidence: 99%
“…Overall, a limited literature base exists on how offenders change over time, and how these changes affect recidivism. 1 One study conducted by Schlager and Pacheco (2011) examined changes within criminogenic needs at two data points: baseline (entering a community-based corrections program) and then 6 months later, using the Level of Service Inventory–Revised (LSI-R) instrument for a sample of parolees. The study found that parolees changed significantly over this short time period in six criminogenic need areas measured by the LSI-R; the only areas where change did not occur were substance use and emotional well-being.…”
Section: What Do We Know About Criminogenic Needs?mentioning
confidence: 99%
“…Specifically, Raynor found that offenders who had decreased LSI-R scores over supervision time were statistically significantly less likely to recidivate while offenders who had increased LSI-R scores over supervision time were much more likely to reoffend. In a recent examination of whether the LSI-R scales were effective at tracking change in dynamic/criminogenic risk scores, Schlager and Pacheco (2011) compared the scores of 179 parolees at entry into a parole program (e.g., work release; drug treatment) with a second administration approximately 6 months later using paired t tests and repeated-measures analysis of variance (for different community intervention sites). Results indicated an overall significant decrease in total LSI-R score and all of its components except for the Alcohol/Dmg and Emotional/Personal domains from Time 1 to Time 2.…”
Section: Dynamic Risk/criminogenic Need Change Through Interventionmentioning
confidence: 99%
“…Although risk assessment research has moved to the assessment of dynamic risk (or criminogenic need) changes through treatment and/or supervision and how these changes relate to recidivism, aside from a few studies (e.g., Olver & Wong, 2009;Olver et al, 2007;Raynor, 2007;Schlager & Pacheco, 2011), researchers have operated under the assumption that dynamic needs are changeable through treatment. Additionally, no studies have examined whether measures used to assess risk change or remain invariant across assessments at different points in time.…”
Section: The Current Studymentioning
confidence: 99%